Pengaruh Model Pembelajaran Project Based Learning Terhadap Creative Thinking Skill Siswa pada Materi Ekologi Kelas VII - Al Hanafi, Muhamad Iqbal; Agnafia, Desi Nuzul; Anfa, Qurrotul (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The purpose of this study is to determine the Project based learning model effects students' creative thinking skill when studying ecology material. Learning is an important component in developing competent human resources, including creative skill. Creativity is very important in education because it can help provide students to innovate and solve problems in the future.Method – This research method used was quasi-experimental with design research is post-test only control group. Analysis data test using validity, reliability, homogeneity, and normality. Hypothesis testing uses independent sample t test (t-test). The population used was all 7th grade students at SMPN 1 Pangkur. Samples used are Class 7D & 7F with Cluster random sampling technique. The total sample subjects were 50 with each sample consisting of 25.Findings – The results of the study showed differences in the post-test results of the Project-based learning model. The results of validity test on rcount ? rtable (0.230) on a total of 50 samples so it is declared valid. The results of the Cronbach alpha instrument reliability test are 0.66, which means that the instrument used is reliable, the results of the t table test are tcount (1.677) ? ttable (2.100). Average post-test score between the two experimental classes using Project based learning amounting 41,76 and the control class Dirrect instrucsion model amounting 34,24. Based on the test results, it can be said that creative thinking skills in ecological material has an influence on Project Based Learning model. Research Implications – The Project based learning models are able to influence students to improve their creative thinking skills. This is because the project-based learning approach gives students the chance to engage their imaginations while creating projects and really understand the subjects they are studying, particularly ecology. Thus, It can be conclude the project based learning model has effect on creative thinking.